Just community approach to character education: school change or student change? - Sukma, Dina; Ananda, Azwar; Gistituati, Nurhizrah; Daharnis, Daharnis (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
This article focuses on the development of, and research about, a strong democracy education intervention, the Just Community approach. Three questions frame the discussion: 1) Does Just Community change student or do student in these program change their school? 2) How Just Community change student and how Just Community change their school? 3) How can democracy be 'learned' by student in these program? This article begins with a brief history of the Just Community approach, a description of the original developmental model created by Lawrence Kohlberg, some research has been created in European and US. Just Community’s theoretical basis: Piaget’s cognitive development theory and Durkheim’s view of collective socialization. How to run this program? The aim of the program and implementation for education.